Restrictive Attitudes Among School Directors - Arató, Ferenc (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In the following study I present those overt and covert attitudes which we have re-covered based on new evidences of a recently finished research among headmasters and directors in primary schools. We traced restrictive attitudes which deeply infl uence effectiveness, effi - ciency, and equity of school institutions. Attitudes, – which decisively infl uence the quality of schools. Do the revealed attitudes correlate certain operational areas of the school? What areas are infl uenced by these attitudes? What kind of school practices may infl uence these attitudes? What kind of school practices offer context for the observation of decreased volume of restrictive, racist attitudes? We compared the revealed attitudes with the attitudes which we observed among pre-service teachers earlier and how the two sets of attitudes overlaps. We also examined the kinds of – recently – covered restrictive attitudes will affect the student teachers among their new colleagues in their workplaces, in our schools.